2022
DOI: 10.1136/bmj-2021-069741
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 vaccination in pregnancy

Abstract: Pregnancy is an independent risk factor for severe covid-19. Vaccination is the best way to reduce the risk for SARS-CoV-2 infection and limit its morbidity and mortality. The current recommendations from the World Health Organization, Centers for Disease Control and Prevention, and professional organizations are for pregnant, postpartum, and lactating women to receive covid-19 vaccination. Pregnancy specific considerations involve potential effects of vaccination on fetal development, placental transfer of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
75
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(116 citation statements)
references
References 110 publications
7
75
0
6
Order By: Relevance
“…The results that older age, higher education and higher income were associated with higher acceptance of COVID-19 vaccination are in agreement with several studies [ 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results that older age, higher education and higher income were associated with higher acceptance of COVID-19 vaccination are in agreement with several studies [ 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…The study was carried out in only one Teaching Hospital of the biggest metropolis of central Italy, and it might be interesting to propose the same questionnaire in other contexts: hospitals in the suburbs, smaller towns and different Italian regions. In these realities, the results may have been less optimistic given that two of the discriminating factors of knowledge are education level and income [ 36 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In such circumstances, this population‐based cross‐sectional study provided valuable information to help delineate a strategic plan to optimize vaccine uptake and coverage among pregnant individuals. Likewise, previous reports have used similar study designs, as mentioned in the reviews by Kalafat et al 2 and Badell et al 3 Otherwise; we agree with Drs Sriwijitalai and Wiwanitkit that cross‐sectional studies are subject to several limitations, and that future prospective longitudinal studies may overcome such constraints while allowing the analysis and evaluation of additional variables of interest such as changes in the intensity of the COVID‐19 pandemic and factors associated with vaccine hesitancy in any given timeframe.…”
supporting
confidence: 77%
“…Another published study investigating the relationship between COVID-19 vaccination in pregnancy and adverse perinatal outcomes showed no increase in the rate of NICU admission or low Apgar score (24) . Another recent review did not show any relationship between COVID-19 vaccination and adverse perinatal outcomes (25) . Regarding the gestational age and birth weight in women who received the COVID-19 vaccine during pregnancy, our study revealed that the average gestational age of unvaccinated women was longer than that of vaccinated women.…”
Section: Discussionmentioning
confidence: 96%